Grouping Of Universities In Indonesia In 2025 Based On The Qs World University Rankings Ranking Indicator Using The Kohonen Self-Organizing Maps Algorithm - Raihan Athaya Wudd; Zamahsary Martha (UNP Journal of Statistics and Data Science, 2025)
Increasing the competitiveness of higher education is one of the main focuses in facing global competition. One of the important indicators in assessing the quality of higher education institutions is the QS World University Rankings which assesses universities based on indicators such as academic reputation, citations per lecturer, sustainability, and international collaboration. This study aims to group universities in Indonesia that are included in the QS World University Rankings in 2025 using the Kohonen Self-Organizing Maps (SOM) algorithm. The data used consisted of 10 QS assessment indicators for 26 universities in Indonesia. The normalization process is carried out using the min-max method, and the optimal number of clusters is determined using internal validation indices such as Connectivity, Dunn, and Silhouette. The results of the analysis show that the best models form three main clusters. Cluster 1 contains universities with superior performance in reputation and research, cluster 2 contains universities with a fairly balanced medium performance, and cluster 3 consists of universities with low performance in key indicators. The results of this study are expected to be the basis for policy makers and university managers to develop strategies to improve the quality of higher education in a targeted manner.